2019
DOI: 10.1186/s12887-019-1634-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the experiences of parent caregivers of children with chronic medical complexity during pediatric intensive care unit hospitalization: an interpretive descriptive study

Abstract: Background Children with medical complexity (CMC) account for an increasing proportion of pediatric intensive care unit (PICU) admissions across North America. Their risk of unscheduled PICU admission is threefold compared to healthy children, and they are at higher risk of prolonged length of stay and PICU mortality. As a result of their sophisticated home care needs, parents typically develop significant expertise in managing their children’s symptoms and tending to their complex care needs at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 41 publications
3
49
0
11
Order By: Relevance
“…Coordinated care and inclusive communication during hospitalizations for CMC require collaboration among stakeholders to support successful transitions in care. Parents' involvement is key, as they are experts in the care of their children, and often have a sense of intuition about their health and well‐being (Lauver, 2010; Rennick et al, 2019). However, parents in this study reported feeling overlooked and excluded during hospitalizations and worried about intruding when providers and nurses were providing care, similar to another study (Rennick et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Coordinated care and inclusive communication during hospitalizations for CMC require collaboration among stakeholders to support successful transitions in care. Parents' involvement is key, as they are experts in the care of their children, and often have a sense of intuition about their health and well‐being (Lauver, 2010; Rennick et al, 2019). However, parents in this study reported feeling overlooked and excluded during hospitalizations and worried about intruding when providers and nurses were providing care, similar to another study (Rennick et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Some within hospital transitions can be reassuring for parents, particularly when they reflect a child's improving condition, but they may also provoke anxiety by requiring adaptation to a new environment, staff, and approaches to care (Berube et al, 2014; Suleman et al, 2019). Communication and care coordination are crucial during hospital transitions for CMC: poor communication and ineffective care coordination lead to incomplete medical histories, unnecessary and inconsistent testing and treatment, medical errors, frustration for providers and parents, and parental discomfort (Foster et al, 2017; Leary et al, 2020; Rauch, 2018; Rennick et al, 2019). Parents of hospitalized CMC value consistent, regular communication with the care team, regardless of the child's status, without having to ask (Berube et al, 2014; Falkenburg et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6] Parent experiences of communication with nurses, with whom parents engage most frequently and share a caregiving role during hospitalization, influence parent satisfaction with inpatient care and enable a sense of parent inclusion as an integral member of the care team. 7,8 Children themselves have identified nurse behaviors as influential to their hospital experience, including nurses' use of kind words, pain reduction efforts, offering humorous diversion and conversation, promotion of a sense of well-being, attention to basic needs, respectful interactions and treatment as an individual, and giving comfort and reassurance. Importantly, Feng et al 3 parents are fundamental aspects of caregiving, which is primarily relational work that requires time for meaningful interpersonal interactions.…”
mentioning
confidence: 99%